2020
DOI: 10.1038/s41467-020-17357-4
|View full text |Cite
|
Sign up to set email alerts
|

An OTX2-PAX3 signaling axis regulates Group 3 medulloblastoma cell fate

Abstract: OTX2 is a potent oncogene that promotes tumor growth in Group 3 medulloblastoma. However, the mechanisms by which OTX2 represses neural differentiation are not well characterized. Here, we perform extensive multiomic analyses to identify an OTX2 regulatory network that controls Group 3 medulloblastoma cell fate. OTX2 silencing modulates the repressive chromatin landscape, decreases levels of PRC2 complex genes and increases the expression of neurodevelopmental transcription factors including PAX3 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(30 citation statements)
references
References 68 publications
2
28
0
Order By: Relevance
“…Recently, mTORC1 signaling was detected as a downstream effector of OTX2 in Group 3 MB (31). A relationship between mTOR pathway and SHH was also demonstrated for SHH MB (32,33).…”
Section: Resultsmentioning
confidence: 89%
“…Recently, mTORC1 signaling was detected as a downstream effector of OTX2 in Group 3 MB (31). A relationship between mTOR pathway and SHH was also demonstrated for SHH MB (32,33).…”
Section: Resultsmentioning
confidence: 89%
“…Following this principle, inhibition of N-MYC in MYCN-amplified neuroblastoma cell lines induced a differentiation morphology as well as upregulation of neural differentiation genes (Kang et al, 2006;Henriksen et al, 2011;Jiang et al, 2011;Westermark et al, 2011;Hossain et al, 2013). Differentiation phenotypes were also observed upon genetic manipulation of medulloblastoma models (Liu et al, 2017;Cheng et al, 2020;Zagozewski et al, 2020), and MRT models (Betz et al, 2002;Nakayama et al, 2017;Wang et al, 2017). These studies show that reversal of the genetic driver can transform tumor cells to a more mature cell state, possibly reflecting the matured cell type it would have become, had it not become cancerous.…”
Section: Reverse Tumor Modeling and Differentiation Therapymentioning
confidence: 79%
“…(A, B) Expression of 12 of the top genes associated with the undifferentiated (A) and differentiated (B) metaprograms as defined by Hovestadt et al [15] in single cells derived from HDMB03 Group 3 MB tumorspheres. Tumorspheres were previously analyzed by scRNA-seq in Zagozewski et al [101]. The undifferentiated metaprogram is associated with an undifferentiated progenitor state and is characterized by ribosomal and translational initiation/elongation factor genes.…”
Section: Discussionmentioning
confidence: 99%
“…demonstrated that cerebellar organoids can be used to model Group 3 MB and to test the effect of specific genes in modulating tumor growth [98]. Our laboratory recently employed scRNA‐seq to assess heterogeneity in stem cell‐enriched tumorsphere cultures from several newly established Group 3 MB cell lines [101]. These tumorspheres mirrored the specific undifferentiated ‘metaprogram’ associated with Group 3 MB patient samples [15] (Fig.…”
Section: Integrating Genomics and Stem Cell Biology In Search Of Nove...mentioning
confidence: 99%
See 1 more Smart Citation